2014
DOI: 10.1080/1369183x.2013.871492
|View full text |Cite
|
Sign up to set email alerts
|

‘We are Always Thinking of our Community’: Bolivian Hometown Associations, Networks of Reciprocity, and Indigeneity in Washington D.C.

Abstract: Using the case of Bolivian migrants in the Washington D.C. metropolitan area, this article analyses the development of hometown associations and the construction of migrant communities at multiple scales. While research has largely focused on the role of hometown associations (HTAs) in promoting local development in sending countries, HTAs also facilitate civic engagement and shape identity formation in both sending and receiving contexts. The article explores the efforts of HTAs and other migrant organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Recognition, prestige and power on the part of groups of people who organize periodic events have been central to understanding native sociopolitical organization and social dynamics amid economic transformation. Studies of internal and international labour migration in Latin America have shown the persistence of return visits to sponsor feasts in home communities (Guaygua and Hinojosa, 2015; Paerregard, 2010; Strunk, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition, prestige and power on the part of groups of people who organize periodic events have been central to understanding native sociopolitical organization and social dynamics amid economic transformation. Studies of internal and international labour migration in Latin America have shown the persistence of return visits to sponsor feasts in home communities (Guaygua and Hinojosa, 2015; Paerregard, 2010; Strunk, 2014).…”
mentioning
confidence: 99%
“… 3 A similar perspective has been applied in order to grasp the regional and transnational dynamics of smaller saints’ festivities in the region (Goldstein, 2004; Guaygua and Hinojosa, 2015; Paerregard, 2010; Strunk, 2014). …”
mentioning
confidence: 99%
“…Entre otras, encontramos: Veredas, 1998; Aparicio y Tornos, 2010; Garreta y Llevot, 2013; Giró y Mata, 2013; y en referencia a la cuestión de género: Ramírez, 1998;Molina et al, 2013. Otra de las líneas más fructíferas en el análisis de la participación política de los inmigrantes es aquella que considera a las asociaciones de migrantes como un vehículo primordial del proceso de integración. Es ese caso se estudian cuestiones como las relaciones de los poderes públicos con las asociaciones de migrantes o la capacidad de estas entidades de generar recursos de apoyo para su comunidad (Veredas, 2003;Odmalm, 2004;Amelina y Faist, 2008;Strunk, 2014; Cebolla-Boado y López-Sala, 2015), partiendo bien de la perspectiva del capital social, bien de los análisis que enmarcan a estas aso-ciaciones en el paradigma de los nuevos movimientos sociales (Koff, 2005;Morales y Giugni, 2011).…”
Section: La Integración Política De Las Comunidades Migrantes: Entre unclassified
“…Current ways of thinking are insufficient to imagine Andean reciprocity as other than a traditional artifact of a static or antiquated culture. This conceptual weakness produces a problematic understanding of Andean reciprocity, which is not supported by the rich empirical evidence that demonstrates the dynamism, negotiation, and contestation of ayni practices (Gose ; Mayer ; Walsh‐Dilley ), nor by how ayni remains central within shifting livelihood forms that are increasingly mediated through market exchange and migration (Strunk ; Tassi ; Wutich ; and other articles in this dossier). How we theorize Andean reciprocity is also significant because economic exchanges and livelihood formations are an important way through which social relations are enacted, individual and group identities are created and performed, and boundaries around communities are drawn (Angé ; Gose ; Killick ).…”
mentioning
confidence: 99%